A sociolinguistic perspective on language competency of ´Chinese children in Spain - Ou, Yiyun; Taillefer, Lidia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
As second generation immigrants, children of Chinese origin in Spain confront a complicated linguistic setting. The objective of this comparative sociolinguistic research, with the participation of 160 children of Chinese origin, is to analyze their sociolinguistic situation in Malaga (Spain), including both external and internal factors (i.e., socio-economic status, education level, language attitudes, identity, motivations, etc.) that affect their linguistic competency and learning. Our methodology is based on quantitative and qualitative data from questionnaires, observations, tests and interviews to explain the linguistic patterns of immigrant children. Tests were completed also by 40 Spanish children and by 40 native Chinese children.